How do behavioral public policy experts see the role of complex systems perspectives?: An expert interview study - Puukko, Sarmite; Heino, Matti T J; Kostamo, Katri; Saurio, Kaisa; Sniehotta, Falko F.; Hankonen, Nelli (Translational Behavioral Medicine, 2024)
Amidst the global momentum of behavioral insights (BI), there has been a shift from mostly nudge-based BI applications to systemic approaches. This is particularly pressing in public health, where interacting issues regularly produce unanticipated consequences. Regardless, little is known about adopting complex systems approaches in behavioral public policy. This study aims to capture current practices of international BI experts on the definition, application, drivers, and hindering factors in adopting complex systems approaches in public policy. Semi-structured individual expert interviews (n = 12) of international BI experts with extensive experience in educating, cooperating with, and/or advising public servants were analyzed with inductive content analysis. While the working definition of BI aligned with published definitions, experts varied in their descriptions of complex systems approaches and its significance for public policy, including socioecological aspects, systematic BI use across policy stages, recognizing intertwined behavior, and lack of ready-made solutions. They emphasized the importance of systems approaches, identifying drivers (e.g. need for a broader focus) and hindrances (e.g. pressure for quick results). Embracing complex systems in behavioral public policy provides a holistic perspective, extending beyond simple nudges, sometimes presumed as universally applicable. While complexity perspectives would align with policymakers’ worldview, applications require more work to tailor to local situations and to evaluate. Recognizing that, given their distinct expertise content, BI expertise can be quite different from complex systems expertise. The field would benefit from clear descriptions and specialized training for effective integration and advocacy for these approaches.In recent years, the use of behavioral insights (BI) in public policy, including health policy, has been shifting from nudges to more comprehensive approaches. This study examines how international BI experts view the use of complex systems approaches in behavioral public policy. Through interviews with 12 experts advising public servants, we found that while BI definitions align with earlier published definitions, experts interpret and apply complex systems approaches differently. Some consider socioecological factors, advocate applying the systematic use of BI throughout the policy cycle, and for some using complex systems approaches means considering intertwined nature of behavioral phenomena and that there are no one-size-fits-all solutions. Experts stress the importance of a systems approach, identifying drivers (e.g. need for a broader focus, experience-based expertise) and hindering factors (e.g. advisory settings, pressure for quick results) in its implementation. This study presents BI’s evolving role in public policy, highlighting the need for complex systems approaches to address multifaceted societal challenges.